FAIRNESS OF SERVICE, TRUST AND CUSTOMER VALUE AS VARIABLE OF ANTECEDENT OF CUSTOMER LOYALTY WITH CUSTOMER SATISFACTION AS INTERVENING VARIABLE IN PT. BANK JAMBI BRANCH OF MUARA BULIAN - Levi Febri Damayanti; Ade Octavia; Tona Aurora Lubis (Journal of Business Studies and Management Review, 2019)
The purpose of this study was to determine the direct effect of service justice, trust and customer value on customer satisfaction, knowing the direct effect of service justice, trust, customer value, and customer satisfaction on customer loyalty, the indirect effect of service justice, trust, customer value on customer loyalty with customer satisfaction as an intervening variable. The population in this study amounted to 32,842. The number of samples taken was 100 respondents. The research method is a quantitative research using field surveys with interviews and questionnaires. The analytical tool used is path analysis. The results showed that: (1) service justice, trust, and customer value simultaneously and partially had a positive and significant effect on customer satisfaction,(2) service justice, trust, customer value, and customer satisfaction simultaneously have positive and significant influence on customer loyalty, while partial service justice, trust, and customer satisfaction has positive and significant impact on customer loyalty and (3) service justice and trust variables indirectly influence the customer loyalty.